PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DI TOKO RAJA DURIAN TIGA PUTRA - M. Ibni Akil Abdilah; Chaerudin Chaerudin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine and explain the level of consumer satisfaction at the Raja Durian Tiga Putra shop based on service quality and product quality. This research was conducted through a statistical technique approach using IBM SPSS 25, data collection using incidental sampling technique on 100 respondents with research subjects were consumers of Raja Durian Tiga Putra Stores. The data analysis technique used is a scale-range analysis technique and multiple regression analysis. The magnitude of the partial effect of Service Quality on Consumer Satisfaction at Raja Durian Tiga Putra is 0.407 or 40.7%. The magnitude of the partial effect of Product Quality on Consumer Satisfaction at Raja Durian Tiga Putra is 0.336 or 33.6%. Then the magnitude of the effect simultaneously Service Quality and Product Quality have a positive and significant influence on Consumer Satisfaction at Raja Durian Tiga Putra by contributing 0.369 or 36.9% and the remaining 63.1% other contributions are influenced by variables not examined.